Thalamic Melanosis in Goats - Soares, Yanca Góes dos Santos; Silva, Draenne Micarla dos Santos; Nascimento, Maria Jussara Rodrigues do; Firmino, Millena de Oliveira; Alves, Rodrigo Cruz; Olinda, Robério Gomes de; Dantas, Antônio Flávio Medeiros; Galiza, Glauco José Nogueira de (Acta Scientiae Veterinariae, 2021)
Background: Melanosis is a blackened pigmentation resulting from the accumulation of melanocytes in tissues that are not normally pigmented. This change in the color of the organs occurs due to the agglomeration of melanocytes originating from abnormal migration during embryogenesis and does not cause dysfunction to the affected organ. Although melanosis frequently occurs in several species and affects several organs such as the brain and spinal cord leptomeninges, involvement in the thalamus region is unusual. The objective of this work was to report two cases of thalamic melanosis in goats, determining the pathological and histochemical aspects that assist in the diagnosis of this condition. Cases: Two cases of thalamic melanosis in goats were diagnosed. In both cases, the animals had no nervous history disease and clinical signs. The cause of death in cases 1 and 2 was established based on anatomopathological findings and clinical signs being diagnosed with mycoplasmosis and asphyxia, respectively. After fixing and making cross-sections of the brain, a focal lengthy blackened area was observed on the thalamus surface in both cases. Microscopically, lesions in the brain were similar in both cases and exclusively affected the thalamus. These cells had abundant cytoplasm, well delimited with brownish granular pigment. The nuclei were difficult to visualize and in some cells, it was rounded, well-defined, morphologically compatible with melanocytes. Melanocytes were mainly distributed around neurons and often distended the perivascular space of multiple blood vessels. In Fontana Masson staining, the granules in the cytoplasm of these cells stained strongly black. The Prussian Blue, Periodic Acid- Schiff's, Von Kossa, and Giemsa stains were negative, and the pigment remained brown. In the unstained slides, assembled after the deparaffinization and clarification process, it was observed the permanence of cells with blackish-brown pigment in the cytoplasm. In immunohistochemistry, strong immunostaining of pigmented cells with the Anti-MelanA antibodies was observed in both cases. Discussion: The diagnosis of thalamic melanosis in goats was carried out based on the characteristic pathological findings, in which melanin pigments were demonstrated and identified through HE, Fontana-Masson staining, and unstained slides and confirmed by the IHC. The use of complementary histochemical techniques was fundamental for the classification of the pigment as melanin, demonstrating to be an accessible and reliable tool for the diagnosis of pathological processes that lead to the accumulation of pigments and or material in the tissues. The occurrence of melanin in the thalamus may be associated with a failure in the migration of melanoblasts, which would go to the optical pathways or to the thalamus. This erratic migration of melanoblasts can be explained by the fact that the forebrain is the embryogenic origin of the optic and diencephalon pathways. Macroscopically, thalamic melanosis must be differentiated mainly from neoplastic processes such as melanoma and hemangiosarcoma, pigmented fungus infections, Phalaris angusta poisoning, listeriosis, neurocutaneous melanosis, and neuromelanin. It was concluded that thalamic melanosis is an uncommon alteration in goats and although it has been diagnosed as an incidental necropsy finding, should be included in the differential diagnosis of diseases that affect the central nervous system, especially those that have a color change associated with the deposition of pigments in the tissues. Keywords: melanin, necropsy findings, pigment, thalamus. Descritores: melanina, achados de necropsia, pigmento, tálamo. Título: Melanose talâmica em caprinos.